Causes and Impact of Migration : A Sociological Study of Emigration From Kandebash, Baglung, Nepal - Gautam, Tika Ram (Dhaulagiri Journal of Sociology and Anthropology, 2006)
DOI: 10.3126/dsaj.v1i0.285 Dhaulagiri Vol.1 (2005) pp.146-163